ANALISIS PERBANDINGAN PERFOMANSI CODEC G.711, G.722 DAN OPUS PADA IMPLEMENTASI LAYANAN VOICE OVER INTERNET PROTOCOL (VOIP) BERBASIS RASPBERRY PI SERVER MENGGUNAKAN METODE MOS E-MODEL (ITU-T G.107) - Chika Yunita; Baso Maruddani; Wisnu Djatmiko; Ariep Jaenul (Politeknik Caltex Riau, 2021)
The purpose of this research is to implement a Raspberry Pi server-based Voice over Internet Protocol (VoIP) service in a small office using the G.711, G.722 and Opus codecs where these codecs do not have a license (free) and have been integrated in various softphones and to see the sound quality resulting from the communication carried out and to see the quality, voice compression (codec) which is the most appropriate / stable on the Wireless LAN network. In testing this VoIP network using G.722, G.711, and Opus audio codecs based on signal strength (RSSI) on the Wireless LAN network as data to be analyzed using the MOS E-Model ITU-T G.107 method. Call testing is done 10 times on each codec. The average delay is 20,507 ms for the G.722 codec, 20,435 ms for the G.711 codec and 20,492 ms for the Opus codec. The average packet loss was 0.711% for G.722 codec, 0.870% for G.711 codec and 1.427% for Opus codec. Based on the results of calculations using the E-Model ITU-T G.107 MOS method, the average yield is 4,155 for the G.722 codec, 4,133 for the G.711 codec and 4.059 for the Opus codec. Based on the results of calculations using the MOS E-Model method, it is generally found that the G.722 codec has better quality than the three codecs tested, because it is more resistant to packet loss based on signal strength (RSSI) received by each client so that the R Factor conversion to MOS yields the highest average MOS value.